Respostas
respondido por:
1
a resposta está acima no desenho
Anexos:
bbgg2728:
obrigado
respondido por:
1
(x - 4).(x - 4) + 5x.(x - 1) = 16
x² - 4x - 4x + 16 + 5x² - 5x = 16
x² - 8x + 16 + 5x² - 5x = 16
x² - 8x + 5x² - 5x = 16 - 16
x² + 5x² - 8x - 5x = 0
6x² - 13x = 0
x.(6x - 13) = 0
x = 0
6x - 13 = 0
6x = 13
x = 13/6
R.: x = 0 e x = 13/6
***********************************
x² - 4x - 4x + 16 + 5x² - 5x = 16
x² - 8x + 16 + 5x² - 5x = 16
x² - 8x + 5x² - 5x = 16 - 16
x² + 5x² - 8x - 5x = 0
6x² - 13x = 0
x.(6x - 13) = 0
x = 0
6x - 13 = 0
6x = 13
x = 13/6
R.: x = 0 e x = 13/6
***********************************
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás